Kajian Kemampuan Keuangan Rumah Sakit Umum Daerah Sebagai Badan Layanan Umum Dan Pengaruhnya Terhadap Kualitas Pelayanan - Annafi Indra Tama; Kusmiyatno Kusmiyatno (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2019)
This study aims to conduct a study of financial independence after being designated as a Regional Public Service Agency (BLUD) and assess its effects on service quality. The research method used is descriptive method with a quantitative non-experimental approach. The results of this study indicate that the financial independence of hospitals is getting better from year to year after being designated as a regional public service body in 2009, from the results of the study obtained an average value of independence that is equal to 435.62% in the delegate category. Starting from 2009 to 2016 in this study the level of hospital financial independence was at a value of> 100% which entered the category of delegation, meaning that there was no interference at all by the government. As for the quality of hospital services through service quality indicators, namely BOR, TOI, LOS, BTO, NDR and GDR. The results of the BOR, LOS and TOI studies are still at the standard level set by the Indonesian Ministry of Health.